PRODUTION OPTIMIZATION FOR WATER-DRIVE GAS RESERVOIR WITH CO-PRODUCTION TECHNIQUE - TITI MALINDA (NIM: 22215034), MARMORA
A gas reservoir with bottom water drive has a lower recovery factor than the gas resevoir with depletion-drive. Along with the increase in gas demand and the majority of gas reservoirs are water-drive, one of the method that are still being developed to increase the recovey factor in water-drive gas reservoir is by coproduction method. This method produces water with a planned to reduce water influx in the gas column. In this thesis, a conceptual model of gas reservoir with depletion-drive and waterdrive is build and being analyzed its behavior. Co-production technique is applied by adding one water production tubing to the water-drive gas reservoir. As a base case (where reservoir parameters are fixed and sensitivity parameters are only surface parameters), sensitivity analysis are being done with sensitivity parameters are flow rate of water production (Qw) and perforation interval (Hp). Furthermore, experimental design of Plackett-Burman is used to analyze the most influencing parameter of gas recovery factor, with the sensitivity parameters are: reservoir permeability (Kx), permeability anisotropy (Kv / Kh), aquifer volume (Vaq), flow rate of water production (Qw ), gas tubing head pressure (THP), and gas well perforation interval (Hp). From the experimental design will be obtaine a proxy equation that will be used in Monte-Carlo simulation to obtain the tornado chart. From the results of this thesis research, it is found that water production rate is the most influencing parameter on the amount of gas recovery factor in the conceptual model of reservoir gas water-drive of the research, followed by aquifer size, perforation interval, reservoir permeability, permeability anisotropy, and the last one is THP of gas well. The crossplot obtained between RF simulation with RF proxy on base case is not good. This is because the proxy equation that is generated is overfitted